Loss of function IFT27 variants associated with an unclassified lethal fetal ciliopathy with renal agenesis. Issue 7 (27th April 2018) - Quélin, Chloé; Loget, Philippe; Boutaud, Lucile; Elkhartoufi, Nadia; Milon, Joelle; Odent, Sylvie; Fradin, Mélanie; Demurger, Florence; Pasquier, Laurent; Thomas, Sophie; Attié‐Bitach, Tania
Abstract : Ciliopathies comprise a group of clinically heterogeneous and overlapping disorders with a wide spectrum of phenotypes ranging from prenatal lethality to adult‐onset disorders. Pathogenic variants in more than 100 ciliary protein‐encoding genes have been described, most notably those involved in intraflagellar transport (IFT) which comprises two protein complexes, responsible for retrograde (IFT‐A) and anterograde transport (IFT‐B). Here we describe a fetus with an unclassified severe ciliopathy phenotype including short ribs, polydactyly, bilateral renal agenesis, and imperforate anus, with compound heterozygosity for c.118_125del, p.(Thr40Glyfs*11) and a c.352 +1G > T in IFT27, which encodes a small GTPase component of the IFT‐B complex. We conclude that bilateral renal agenesis is a rare feature of this severe ciliopathy and this report highlights the phenotypic overlap of Pallister–Hall syndrome and ciliopathies. The phenotype in patients with IFT27 gene variants is wide ranging from Bardet–Biedl syndrome to a lethal phenotype.